Direct Manager-Employee Relationship and Job Satisfaction in Start-Up Businesses - Rachel Natalie G. Simanjuntak; Henndy Ginting (Journal Research of Social Science, Economics, and Management, 2025)
Start-up businesses, characterized by lean structures and limited resources, necessitate multifaceted roles for managers, often leading to informal human resource responsibilities. This research explores three key questions: how manager-employee relationships are formed in start-ups, what job satisfaction entails in such environments, and the relationship between the quality of these interactions and employee job satisfaction. Given that start-ups often lack formal HR structures, strong relational foundations are critical for engagement and organizational stability. The study employs a qualitative approach, utilizing semi-structured interviews with participants from various Indonesian start-ups. NVivo software facilitated coding and thematic analysis, grounded in the Leader Member Exchange (LMX) theory and Job Satisfaction theory by McShane and Von Glinow. Findings reveal that quality relationships are defined by trust, respect, and obligation, with trust emerging from employees' confidence in managerial competence, while respect is shown through acknowledgment and fairness. Job satisfaction is influenced by job characteristics, supportive work environments, and emotional experiences. Despite heavy demands, employees experience high satisfaction when interpersonal support is prevalent. A strong connection between LMX and job satisfaction suggests that relational quality can mitigate structural limitations, ultimately enhancing employee well-being in early-stage organizations. This research offers insights for strengthening relational practices, highlighting the significance of manager-employee relationships in influencing job satisfaction.